Racial Disparities in Adverse Neonatal Outcomes After Elective Induction of Labor: A Population-Based Study [235]. (May 2015) - Vilchez Lagos, Gustavo Alexander; Gill, Navleen; Jaramillo, Helen; Dai, Jing; Sokol, Robert J.
Abstract : OBJECTIVE: The current recommendation regarding the optimal timing for elective induction of labor is to await 39 weeks and above to decrease prematurity risks. Variations in fetal maturation rates and obstetric outcomes according to ethnicity and race are well documented. The objective was to analyze the effect of maternal race on neonatal outcomes after elective induction of labor. METHODS: Singleton deliveries after elective induction of labor at term (37–42 weeks of gestation) were selected from the National Center for Health Statistics Birth Cohorts 2007–2010. Cases with congenital anomalies, hypertensive or diabetic disorders, low birth weight, breech presentation, or premature preterm rupture of membranes were excluded. Adverse neonatal outcomes analyzed included: Apgar score, assisted ventilation, neonatal intensive care unit admission, surfactant or antibiotic use, neonatal seizures, and birth injury. Frequencies of neonatal outcomes were calculated for the overall population and according to race: whites, blacks, Native Americans, and Asians. RESULTS: A total of 2, 556, 464 cases were included for analysis: 2, 094, 489 whites, 328, 114 blacks, 25, 908 Native Americans, and 107, 953 Asians. For the overall population and whites, the distribution of adverse neonatal outcomes frequencies is U-shaped with the nadir at 39 weeks of gestation, as previously described in the literature. However, for the minority groups (blacks, Native Americans, and Asians), the distribution is also U-shaped, but with the nadir of neonatal complications mostly at 38 weeks of gestation. CONCLUSION: We provide more evidence that neonatal outcomes vary according to race, most likely as a result of a difference in maturity rates. Maternal race should be considered in the optimal timing for elective obstetric interventions. Further studies focusing on minorities and postmaturity risks are warranted.